Has the burden of depression been overestimated? - Michelle E. Kruijshaar; Nancy Hoeymans; Jan Spijker; Marlies E.A. Stouthard; Marie-Louise
OBJECTIVE: To investigate whether high estimates of the burden of depression could be attributed to an overestimation of disability weights (reflecting more severe disability). METHODS: We derived disability weights that were tailored to prevalence data. Empirical disability data from a Dutch community survey was used to describe three classes of severity of depression and their proportional prevalence. We obtained valuations from experts for each class and calculated the overall disability weight for depression. FINDINGS: Expert valuations were similar to those of previous studies. The overall disability weight for depression was similar to other studies except the 1994 Dutch Burden of Disease Calculation, which it exceeded by 73%. The lower Dutch 1994 disability weight resulted from an overestimation of the proportion of mild cases of depression by experts (60% versus 27% observed in the empirical data used in the present study). CONCLUSION: This study found no indication that disability associated with depression was overestimated. The Dutch example showed the importance of tailoring disability weights to epidemiological data on prevalence.